The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.wem.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Chemical Cold Packs for Treatment of Exercise-Induced Hyperthermia: A Randomized Controlled Trial

Abstract: Application of CCP to glabrous skin surfaces was more effective for treating exercise-induced heat stress than the traditional CCP cooling intervention. This novel cooling technique may be beneficial as an adjunctive treatment for heat-related illness in the prehospital environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For the critical outcome of rate of core body temperature reduction, we identified moderate-certainty evidence (downgraded for risk of indirectness) from 1 non-RCT 35 recruiting 10 adults with exertional hyperthermia. This small study reported a faster rate of core body temperature reduction associated with the use of commercial ice packs to the facial cheeks, palms, and soles compared with passive cooling (MD, 0.18 C/min; 95% CI, 0.12À 0.24).…”
Section: Commercial Ice Packsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the critical outcome of rate of core body temperature reduction, we identified moderate-certainty evidence (downgraded for risk of indirectness) from 1 non-RCT 35 recruiting 10 adults with exertional hyperthermia. This small study reported a faster rate of core body temperature reduction associated with the use of commercial ice packs to the facial cheeks, palms, and soles compared with passive cooling (MD, 0.18 C/min; 95% CI, 0.12À 0.24).…”
Section: Commercial Ice Packsmentioning
confidence: 99%
“…We identified moderate-certainty evidence (downgraded for risk of indirectness) from 1 controlled trial 35 recruiting 10 adults with Intravenous Fluids. With the exception of the single study of ice-water immersion, for the critical outcome of mortality and the important outcomes of clinically important organ dysfunction, adverse events, and hospital length of stay, there were no comparator studies evaluating any of the previously mentioned cooling techniques.…”
Section: Commercial Ice Packsmentioning
confidence: 99%
See 1 more Smart Citation
“…99,100 Ice packs have been found to have greater cooling capacity than chemical cold packs, 101 and if used, are most efficacious when wet and covering the entire body (to optimize conductive cooling). 99 A small translational study applied chemical cold packs to the glabrous skin of the palms, soles, and cheeks and found twice the cooling rate over traditional major vascular locations, 102 using the high-capacity blood flow of the subcutaneous arteriovenous anastomoses.…”
Section: Chemical Cold Packs/ice Packsmentioning
confidence: 99%
“…In human studies, the use of chemical cold packs with a temperature of 13 • C was not associated with vasoconstriction in non-haired skin areas, therefore cool packs rather than ice packs would be recommended. 31 Other non-invasive methods would be placing a fan near the patient to dissipate heat via convection; evidence on how effective this is in dogs is limited. In this case, the inbuilt fan system in MRI was on maximum flow, an additional freestanding fan would have been impractical for safety reasons.…”
Section: Active Coolingmentioning
confidence: 99%